Development of education and discovery of Tuberculosis case community-based in Tulungagung Regency (Berita Kedokteran Masyarakat (BKM), 2020)
Background: WHO data shows an increase in estimated Tuberculosis cases per year in Indonesia, from 331,703 in 2015 to 563,879 in 2018 (70%). It includes an increase of 121,707 (28%) between 2017 and 2018. In the development of pulmonary TB in Tulungagung Regency, the number of suspected cases of pulmonary TB was 4,122 in 2016 and 4,419 in 2017. The number of BTA+ cases was 323 in 2016 and 478 in 2017. The population in 2016 was 1,026,101 people, while in 2017 the population was 1,030 .790 people. In monitoring and assistance from the community side, there are no applications that can be used to share, including the role of the community in independent detection. Objective: Designing educational applications and discovery of community-based Tuberculosis cases in Tulungagung. Method: Qualitative and quantitative research with action research design. The study subjects were two managers of the tuberculosis program, three people of SIK manager, four sectors, three people of tuberculosis manager, three people of tuberculosis who had recovered, or three people tuberculosis cadre. Results: This research resulted in the design of Community Based Tuberculosis Education and Discovery Application Cases. For education, display in the form of text, images, and videos, while for case finding in input and output. User Experience Questionnaire test results show the results of attractiveness, pragmatic quality, and hedonic quality on a normal scale. Conclusion: Applications can support partnerships, cross-sectoral, community needs a set of systems functioning in monitoring, dissemination, and increasing screening independently by the community or cadres in tuberculosis prevention.Keywords: Edutebe Apps, Health Information System, Public Health, Action Research, Active Case Finding Tuberculose.